(untitled) (Bangladesh Medical Journal, 2016)
Appropriate ante-natal care services promote safe motherhood and delivery with improved maternal and neonatal outcome. This population based cross sectional descriptive study was carried out to determine the utilization of antenatal care (ANC) services in a rural community of Bangladesh. Out of the 112 women studied, 63.4% mothers were found to receive antenatal care. Among them one third (32.4%) took it more than 4 occasions, 34(47.8%) pregnant women received antenatal care from government hospitals, 19(27%) from family welfare centre, 6(8.5%) from satellite clinics and around 12(17%) received from private hospitals. Around 71% mothers received ANC service from doctor while 17% mothers received from trained professionals. Seventy four percent mothers received tetanus (TT) injections. Only one fourth (25.3%) mothers had not received it. On an average, 90% mothers received iron tablets during their pregnancy. Regarding have danger signs during pregnancy, it was found that, 58.9% mothers were not aware about the have danger signs and 29.5% respondents knew about all the danger signs. Association between educational status and treatment seeking behaviour for pregnancy complication was found to be statistically significant (p<0.05). However, association between educational status and place of treatment for pregnancy complication was also found significant (p<0.01). Intensive awareness programme, behavioural change interventions and regular pregnancy monitoring may promote antenatal care service utilization in rural Bangladesh. Bangladesh Med J. 2015 May; 44 (2): 67-71